2003
DOI: 10.1111/j.1365-2621.2003.tb08259.x
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid and Sodium Citrate Effects on Reducing Pink Color Defect of Cooked Intact Turkey Breasts and Ground Turkey Rolls

Abstract: The ability of citric acid (0.1%, 0.2%, 0.3%) and sodium citrate (1.0%) to reduce the pink color defect induced with sodium nitrite (1 ppm, 5 ppm, 10 ppm) and nicotinamide (0.5%, 1.0%) in cooked, intact turkey breasts and ground turkey rolls was examined. Citric acid at 0.2% and 0.3% and sodium citrate consistently reduced natural or induced pink color in ground turkey rolls but had no effect on pink color of intact turkey breasts. Citric acid reduced pH and cooking yields, whereas sodium citrate did not. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Mb concentrations and buffer pH reflected concentration of Mb and typical pH in beef (Gatellier, Hamelin, Durand, & Renerre, 2001) and turkey meat relevant to PCD (0.04 mmol/L, Niewiarowicz, Pikul, & Czajka, 1986; pH 6.2, Sammel & Claus, 2003). The pH reported for cooked turkey breast was in the range of 6.22-6.31 (Sammel & Claus, 2003). Therefore, pH 6.2 was selected for turkey Mb model system in the present study.…”
Section: Thermostability Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Mb concentrations and buffer pH reflected concentration of Mb and typical pH in beef (Gatellier, Hamelin, Durand, & Renerre, 2001) and turkey meat relevant to PCD (0.04 mmol/L, Niewiarowicz, Pikul, & Czajka, 1986; pH 6.2, Sammel & Claus, 2003). The pH reported for cooked turkey breast was in the range of 6.22-6.31 (Sammel & Claus, 2003). Therefore, pH 6.2 was selected for turkey Mb model system in the present study.…”
Section: Thermostability Assessmentmentioning
confidence: 98%
“…The residual sodium hydrosulfite was removed and the pH was adjusted to 6.2 and 5.6 for turkey and beef OxyMb respectively, by passing through PD-10 desalting columns equilibrated with 50 mmol/L sodium citrate buffer at corresponding pH. Mb concentrations and buffer pH reflected concentration of Mb and typical pH in beef (Gatellier, Hamelin, Durand, & Renerre, 2001) and turkey meat relevant to PCD (0.04 mmol/L, Niewiarowicz, Pikul, & Czajka, 1986; pH 6.2, Sammel & Claus, 2003). The pH reported for cooked turkey breast was in the range of 6.22-6.31 (Sammel & Claus, 2003).…”
Section: Thermostability Assessmentmentioning
confidence: 99%
“…Slesinski et al (2000a) reported that nonfat dry milk reduced CIE a* values in cooked turkey breasts containing 10 ppm sodium nitrite, while dairy proteins reduced CIE a* values in nicotinamide-treated samples. Sammel and Claus (2003a) found that 2% to 3% citric acid and 1.0% sodium citrate reduced the pink color developed by sodium nitrite and nicotinamide in ground turkey rolls, but unaffected the pink color of intact turkey breasts. However, these studies did not mimic the practical processing conditions that generated the naturally occurring pink color without pink generating ligands.…”
Section: Introductionmentioning
confidence: 93%
“…2, 2020 232 Helmke and Froning, 1971;Howe et al, 1982;Mugler et al, 1970;Nam and Ahn, 2002a;Nam and Ahn, 2002b;Nash et al, 1985). Due to the numerous factors involved and the sporadic occurrence of pink color defect, previous studies attempted to eliminate or reduce the pink color defect using non-meat ingredients (Dobson and Cornforth, 1992;Kieffer et al, 2000;Sammel and Claus, 2003a;Sammel and Claus, 2003b;Sammel and Claus, 2007;Schwarz et al, 1999;Slesinski et al, 2000a;Slesinski et al, 2000b). These studies indicated that some non-meat ingredients were effective in reducing the pink color in the cooked products which resulted from the addition of pink color generating ligands (nitrite or nicotinamide) to the meat system.…”
Section: Introductionmentioning
confidence: 99%
“…Pink colour defect is a quality problem in turkey which results in an uncooked pink appearance in fully cooked, uncured meat products, such as turkey rolls (Cornforth, Vahabzadeh, Carpenter, & Bartholomew, 1986) and intact turkey breasts (Sammel & Claus, 2003). Consumers often relate the pink appearance to an uncooked product, although microbiological safety of such products is assured.…”
Section: Introductionmentioning
confidence: 99%